2005
DOI: 10.1002/ajh.20285
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IAP-family proteins in adult acute mixed lineage leukemia (AMLL)

Abstract: Inhibitor of apoptosis protein (IAP)-family proteins suppress apoptotic signaling in normal/neoplastic cells in various settings. To determine the apoptosis-resistant mechanism in adult acute mixed lineage leukemia (AMLL) with biphenotypic blasts responsible for resistance against chemotherapy, the expression levels of IAP-family proteins in AMLL bone marrow cells were analyzed by quantitative RT-PCR. The overall expression levels of IAPs were higher than those in control, AML, and ALL cells. A significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 36 publications
(42 reference statements)
2
22
0
2
Order By: Relevance
“…The exact role of IAPs in acute leukemia is complicated by the fact that they have been found to display variable expression and to play different roles in chemosensitivity and chemoresistance. IAP expression, determined by quantitative reverse transcription-PCR, was found to be higher in drug-resistant adult acute mixed lineage leukemia (AMLL) than in ALL and AML cells, and the expression of survivin, NAIP, and XIAP was higher in AMLL than ALL (44). Other investigators found XIAP and c-IAP-1 to be differentially expressed among AML patients with an absence of NAIP mRNA (45).…”
Section: Molecular Cancer Therapeutics 1957mentioning
confidence: 97%
“…The exact role of IAPs in acute leukemia is complicated by the fact that they have been found to display variable expression and to play different roles in chemosensitivity and chemoresistance. IAP expression, determined by quantitative reverse transcription-PCR, was found to be higher in drug-resistant adult acute mixed lineage leukemia (AMLL) than in ALL and AML cells, and the expression of survivin, NAIP, and XIAP was higher in AMLL than ALL (44). Other investigators found XIAP and c-IAP-1 to be differentially expressed among AML patients with an absence of NAIP mRNA (45).…”
Section: Molecular Cancer Therapeutics 1957mentioning
confidence: 97%
“…This may suggest that cross resistance more likely developed in BAL patients than in AML or ALL patients, causing a poor response to treatment and short survival period. Nakagawa et al 23 found that the overall expression levels of inhibitor of apoptosis protein (IAP)-family proteins in BAL bone marrow cells were higher than those in control, AML, and ALL cells. These results partly supported our observations.…”
Section: Discussionmentioning
confidence: 99%
“…60 In adult acute mixed-lineage leukemia, higher expression levels of XIAP and survivin were detected, compared with their expression levels in ALL, indicating that higher levels of several IAP proteins may contribute to the chemotherapy-resistant nature of this type of leukemia. 61 Immunohistochemical analysis of XIAP in diffuse large B-cell lymphoma showed that XIAP overexpression occurred in 55% of the diffuse large B-cell lymphomas and was significantly associated with adverse clinical outcome. 62 Moreover, elevated c-IAP2 mRNA levels were detected in mature neutrophils from a patient with chronic neutrophilic leukemia, but not in neutrophils from patients with chronic myelogenous leukemia.…”
mentioning
confidence: 99%